Stochastic modeling of central apnea events in preterm infants - Clark, Matthew T. (Physiol Meas, 2016)
A near-ubiquitous pathology in very low birth weight infants is neonatal apnea, breathing pauses with slowing of the heart and falling blood oxygen. Events of substantial duration occasionally occur after an infant is discharged from the NICU. It is not known whether apneas result from a predictable process or from a stochastic process, but the observation that they occur in seemingly random clusters justifies the use of stochastic models. We use a hidden-Markov model to analyze the distribution of durations of apneas and the distribution of times between apneas. The model suggests the presence of four breathing states, ranging from very stable (with an average lifetime of 12 hours) to very unstable (with an average lifetime of 10 seconds). Although the states themselves are not visible, the mathematical analysis gives estimates of the transition rates among these states. We have obtained these transition rates, and shown how they change with post-menstrual age; as expected, the residence time in the more stable breathing states increases with age. We also extrapolated the model to predict the frequency of very prolonged apnea during the first year of life. This paradigm – stochastic modeling of cardiorespiratory control in neonatal infants to estimate risk for severe clinical events – may be a first step toward personalized risk assessment for life threatening apnea events after NICU discharge.